2019
DOI: 10.1590/s1980-6574201900010021
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Improves Heart Rate Recovery after Exercise in Hypertension

Abstract: This study tested the hypothesis that: 1-the exercise training would improve the heart rate recovery (HRR) decline after maximal exercise test in hypertensive patients and; 2-the exercise training would normalize HRR decline when compared to normotensive individuals. Methods: Sixteen hypertensive patients were consecutively allocated into two groups: Exercise-trained (n = 9, 47±2 years) and untrained (n = 7, 42±3 years). An exercise-trained normotensive group (n = 11, 41±2 years) was also studied. Heart rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Adicionalmente, observou-se que a FCR desses pacientes foi normalizada quando comparada àquela de indivíduos normotensos. Esses resultados indicam de maneira significativa um efeito terapêutico do treinamento físico na função autonômica cardíaca desses pacientes hipertensos (Vicente et al, 2019).…”
Section: Discussionunclassified
“…Adicionalmente, observou-se que a FCR desses pacientes foi normalizada quando comparada àquela de indivíduos normotensos. Esses resultados indicam de maneira significativa um efeito terapêutico do treinamento físico na função autonômica cardíaca desses pacientes hipertensos (Vicente et al, 2019).…”
Section: Discussionunclassified
“…Furthermore, differences in heart rate recovery may vary in elderly hypertensive individuals depending on BP control. Amaro-Vicente et al [37] investigated heart rate recovery in normotensive and hypertensive individuals whose mean age was over 57 years using antihypertensive drugs with controlled and uncontrolled blood pressure. They found that in hypertensive patients, the ideal BP after antihypertensive medication is related to an improvement in sympathetic/vagal balance [38].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic-exercise training is recommended for the treatment of hypertension. In addition to decrease blood pressure, aerobic training improves resting cardiovascular autonomic modulation in hypertensives and accelerates HRR after exercise [4]. However, the effects of aerobic training on autonomic control may vary depending on the time of day in which training sessions are performed.…”
Section: Introductionmentioning
confidence: 99%